Whole-Exome Sequencing and hiPSC Cardiomyocyte Models Identify MYRIP, TRAPPC11, and SLC27A6 of Potential Importance to Left Ventricular Hypertrophy in an African Ancestry Population - Irvin, Marguerite R.; Aggarwal, Praful; Claas, Steven A.; de las Fuentes, Lisa; Do, Anh N.; Gu, C. Charles; Matter, Andrea; Olson, Benjamin S.; Patki, Amit; Schwander, Karen; Smith, Joshua D.; Srinivasasainagendra, Vinodh; et al. (Frontiers in Genetics, 2021)
Background: Indices of left ventricular (LV) structure and geometry represent useful intermediate phenotypes related to LV hypertrophy, a predictor of cardiovascular disease outcomes. Methods and Results: We conducted an exome-wide association study of LV mass adjusted to height2.7, LV internal diastolic dimension, and relative wall thickness among 1,364 participants of African ancestry (AAs) in the Hypertension Genetic Epidemiology Network (HyperGEN). Both single-variant and gene-based sequence kernel association tests were performed to examine whether common and rare coding variants contribute to variation in echocardiographic traits in AAs. We then used a data-driven procedure to prioritize and select genes for functional validation using a human induced pluripotent stem cell cardiomyocyte (hiPSC-CM) model. Three genes (myosin VIIA and Rab interacting protein [MYRIP], trafficking protein particle complex 11 [TRAPPC11], and solute carrier family 27 member 6 [SLC27A6]) were prioritized based on statistical significance, variant functional annotations, gene expression in the hiPSC-CM model, and prior biological evidence and were subsequently knocked down in the hiPSC-CM model. Expression profiling of hypertrophic gene markers in the knockdowns suggested a decrease in hypertrophic expression profiles. MYRIP knockdowns showed a significant decrease in atrial natriuretic factor (NPPA) and brain natriuretic peptide (NPPB) expression. Knockdowns of the heart long chain fatty acid transporter SLC27A6 resulted in downregulated caveolin 3 (CAV3) expression which has been linked to hypertrophic phenotypes in animal models. Finally, TRAPPC11 knockdown was linked to deficient calcium handling. Conclusions: The 3 genes are biologically plausible candidates that provide new insight to hypertrophic pathways.